2000
DOI: 10.1359/jbmr.2000.15.10.1924
|View full text |Cite
|
Sign up to set email alerts
|

Force-Induced Osteoclast Apoptosis In Vivo Is Accompanied by Elevation in Transforming Growth Factor β and Osteoprotegerin Expression

Abstract: The mechanism controlling the disappearance of osteoclasts from bone surfaces after bone resorption in vivo is largely unknown. This is because there is no suitable experimental system to trace the final fate of osteoclasts. Here, we used an experimental model of tooth movement in rats to show that preexisting osteoclasts disappeared from the bone surface through apoptosis during a force-induced rapid shift from bone resorption to formation. On the distal alveolar bone surface of the maxillary molar in growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 54 publications
6
80
0
1
Order By: Relevance
“…The mechanical environment, for example, can be one possible origin of cell stimulation. In fact, it is known that moderate mechanical loading stimulates two crucial phenomena in periimplant bone healing: osteogenic cell differentiation (Carter and Giori, 1991;Palma et al, 2005;Ignatius et al, 2005), quantified by α mb in our model, and growth factor secretion (Raab-Cullen et al, 1994;Yeh et al, 1994;Kobayashi et al, 2000), denoted by α 2 . According to these experimental results, an hypothetical rise of the level of mechanical stimulation would lead to an increase of χ and, thus, χ could be considered to some extent as a measure of mechanical stimulation (see Fig.…”
Section: Discussionmentioning
confidence: 85%
“…The mechanical environment, for example, can be one possible origin of cell stimulation. In fact, it is known that moderate mechanical loading stimulates two crucial phenomena in periimplant bone healing: osteogenic cell differentiation (Carter and Giori, 1991;Palma et al, 2005;Ignatius et al, 2005), quantified by α mb in our model, and growth factor secretion (Raab-Cullen et al, 1994;Yeh et al, 1994;Kobayashi et al, 2000), denoted by α 2 . According to these experimental results, an hypothetical rise of the level of mechanical stimulation would lead to an increase of χ and, thus, χ could be considered to some extent as a measure of mechanical stimulation (see Fig.…”
Section: Discussionmentioning
confidence: 85%
“…It has been shown that mechanical loading has the ability to suppress bone resorption (3,8,12,26). However, the cellular mechanism that underlies this anti-resorptive effect is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Physical loading and routine activities have been shown to inhibit bone resorption that would otherwise occur with disuse (3,8,12,26). However, the cellular mechanism underlying this phenomenon remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5). Several findings also indicate that compressive forces induce apoptosis [34,35], thus suggesting that external forces play a role in pulp volume reduction.…”
Section: Apoptosis In Intact Human Teeth At the Beginning Of Secondarmentioning
confidence: 98%